Star Sticker Rewards' Influence On Group B Children’s Arts Learning Discipline At The Dharma Wanita Kindergarten Bendunganjati - ummah, nahdiyatul; Fauziah, Syifa (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2023)
The discipline of group B students at the Dharma Wanita Bendunganjati Kindergarten, which had not developed effectively, served as the driving force for this study. The pretest findings, which indicate that 12 of the 19 children's disciplines still meet the criterion for not progressing, are evidence of this. An experimental research model is combined with a quantitative research method to conduct this study. One group pretest-posttest, or one group study with a sample of 19 children, was the type of experiment that was used in this work. This is evident from the average improvement in children's discipline before and after therapy, which is 26.6 to 55.1, based on the research results, sig < 0.05, or 0.000. Therefore, H0 is refused, and H1 is approved, indicating that rewarding children with star stickers impacts their behavior both before and after therapy. Based on the conducted research, it can be inferred that rewarding group B children at Dharma Wanita Bendunganjati Kindergarten with star stickers affects their behavior.